Analisis Pemilihan Bahan Baku Produksi Tahu (Kajian Nilai Tambah Produksi Kedelai Lokal dan Kedelai Impor) - Untari, Wiwik Sri; Fitriyaningsih, Fitriyaningsih; Muhlis, Abdullah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Tofu agroindustry is a business that has very good and profitable prospects. Because tofu is a food source that is high in protein and is in great demand by the public, the demand for tofu is increasing. This high demand certainly has an impact on the need for soybean raw materials. To find out the added value of local and imported processed soybean products, it is important to carry out research to determine the high or low added value produced by a business using different types of soybean raw materials. The aim of the research is to analyze how much income the tofu agro-industry uses local soybeans and imported soybeans as raw materials, to analyze how much added value the agro-industry uses local and imported soybeans as raw materials in Situbondo Regency. West, Central and East are tofu production centers spread across Situbondo Regency with a total of 50 tofu agro-industry respondents. The research method used is descriptive and analytical methods. The data analysis used is income analysis and added value analysis using the Hayami method. The research results show 1) The income of the tofu agroindustry made from local and imported soybeans is each profitable, for local soybeans Rp. 1,107,288,- while imported soybeans are Rp. 1,985,152.-2) The use of local soybean raw materials is an average of 103 kg/production process resulting in an average of 109 tofu boards per production with an added value of Rp. 8,682,-/kg, the value added ratio of local soybeans is 37% in the medium category. Meanwhile, imported soybean raw materials average 172 kg/production process producing an average of 143 tofu planks/production process with an added value of IDR. 10,256/kg, the added value ratio of imported soybeans is 42% in the high category.